ANALISIS BIAYA PROJEK KONSTRUKSI DI INDONESIA DALAM PERSPEKTIF SYARIAH - Sedayu, Agung (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2010)
The monetary circulation in construction projects is very important to be analyse and evaluated from the perspective of islamic law. This is so because most construction companies were indicated practicing some methods which have no basis in Islam. Some of them are even legally done some practice which considered as forbidden in Islam, such as dishonesty, manipulations, and injustice acts. Moreover, in Indonesia most of construction companies are using a foreign method from the former collonial government. The methods are found to be generating conflicts between persons in the project, and therefore could damage the social relationship of human being. BOW Analysis, and SNI which developed from BOW are still used in Indonesia. Those methods are not able yet to stand for some essential human rights, especially for the projects’ labor. The same condition happens too in the modern-world analysis which have coeffecients in determining worker fee, such as Weibull Analysis. This very sophisticated analysis is unable to answer the economic problems of society. All these methods were developed under the capitalistic framework which only intended to obtain more individual benefit, without considering the loss resulted to other people’s lives. Labor’s payment is very low in this capitalistic construction analysis. They are assumed similar to machines and equipments which has a range of productivity. If they became unproductive after some period of time, they can be thrown easily without considering their lives needs. On the other side, economic system in Islamic law is provided with some solutions to answer all social and economical problems in the society. Shariah economic and management system which is applied in a construction corporation’s system analysis and accountancy will bring great advantages, whether for its labor and company, or for society in general. Within the shariah construction management, all parties will reach Allah’s blessing and gain benefits in both worldly life and the hereafter.